Physical-chemical and morphological characterization of the pildoro (musa acuminata) produced in a lowland and highland zone in the department of Caquetá, with the purpose of proposing transformation processes. (@limentech, Ciencia y Tecnología Alimentaria, 2019)
Pildoro, known as Musa acuminata, is a fruit that in the Department of Caquetá has been cultivated by farmers in the Vega y Lomerío sector; but at the same time it has not been given an added value; this may be due to the lack of knowledge on the part of the population about the nutritional properties it possesses. The objective of this study was to propose transformation processes for small farmers in the region.transformation processes to small farmers in the region as an alternative to strengthen their economy. For this purpose, three samplings were carried out in the Vega and Lomerío zones; cultivation sites established by the Agrocaquetá association. ThusLikewise, some physicochemical parameters were determined and compared in the different sampling sites, which allowed a comparison to be made based on the guidelines established in Resolution 3929 of 2011.Initially, the following parameters were determined for the Vega and Lomerío zones, respectively: Brix (16.7 °Brix and 27.6 °Brix), moisture (36.8% and 44.6%), pH (4.2 and 5) and density (1.323 g/ml and 0.922 g/ml). Morphological parameters such as volume (52 ml and 58 ml), length (7.4 cm and 8.5 cm), percentage of pulp (86.1 % and 84.3 %) were evaluated. It was possible to establish a wide difference between the two zones in percentage of moisture, density, brix degrees and volume; to suggest transformation processes: Jams, Jellies and Snacks for their high brix degrees content. Achieving to give an added value improving its development and commercialization within the region.
Keywords: Characteristics; Pildoro; Physico-chemical; morphological; Transformation